The impact of pharyngocutaneous fistula on the survival of patients submitted to total laringectomy - Rios, Guilherme (2023)
Objectives: The pharingocutaneous fistula (FFC) is an important post-operatory complication after total laryngectomy (LT), often associated with an increase in peri-operatory morbidity. Studies about the impact of FFC on long-term survival on patients submitted to LT remain scarce. The objective of this work was to study the relation between the presence of FFC and the survival rate of patients submitted to total laryngectomy. Material and methods: A retrospective cohort study was performed on patients submitted to LT between January 2013 and December 2017. The evaluation of survival and associated risk was preformed through a Kaplan-Meier analysis and multivariate Cox regression.   Results: 50 patients were included, with an average follow-up time of 67 months. The overall survival and disease-free survival were similar between the two groups, with no significant statistical difference. Conclusions: Our study didn’t find any relation between the presence of FFC and the survival rates of patients submited to LT.